MORPHOLOGICAL AND ECOLOGICAL OBSERVATIONS ON CHIROMANTIS VITTIGER (ANURA: RHACOPHORIDAE) IN MOUNT HALIMUN - SALAK NATIONAL PARK, INDONESIA - Mirza Dikari Kusrini; Muhammad Irfansyah Lubis; Boby Darmawan; Luthfia Nuraini (BRIN Publishing (Penerbit BRIN), 2017)
Despite an early description, the rhacophorid frog (Chiromantis vittiger (Boulenger 1897)) is relatively poorly known species. It has been found in several areas in the mountainous part of western Java, one of which is in the Chevron Geothermal Indonesia (CGI) concession area within Mount Halimun-Salak National Park. An ecological study of this species and its habitat was conducted in CGI from April to September 2008. The biological and ecological aspects of this tree frog such as morphology, habitat characteristics, breeding behaviour, and larval development are presented in this paper. This study found that the fertilised eggs hatch as free-swimming tadpoles. In addition, the availability of artificial habitat in the form of concrete ponds helps sustain the population throughout the year. We also report parental care in this species.